2004
DOI: 10.1002/j.1556-6678.2004.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Marital Characteristics, Marital Interaction Processes, and Marital Satisfaction

Abstract: Structural Equation Modeling techniques were used to clarify the relationship between marital characteristics, marital processes, and the dependent variable—marital satisfaction—in a sample of 201 participants who were in 1st marriages. The Dyadic Adjustment Scale (DAS; G. B. Spanier, 1976) and the Enriching and Nurturing Relationship Issues, Communication and Happiness Inventory (ENRICH; D. H. Olson, D. G. Fournier, & J. M. Druckman, 1987) provided scales to measure marital interaction processes and marital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 30 publications
3
77
1
7
Order By: Relevance
“…Married couple's values have an important role in ensuring satisfaction in marriages and relationships between spouses. The process of interaction of marriage and marital satisfaction is related to the features of marriage and individual satisfaction in the marriage relationship (Rosen-Grandon, Myers and Hattie, 2004). To have values such as trust, devotion and docility of the spouses have contributed to the continuing marital relationship in a healthy way.…”
Section: Discussionmentioning
confidence: 99%
“…Married couple's values have an important role in ensuring satisfaction in marriages and relationships between spouses. The process of interaction of marriage and marital satisfaction is related to the features of marriage and individual satisfaction in the marriage relationship (Rosen-Grandon, Myers and Hattie, 2004). To have values such as trust, devotion and docility of the spouses have contributed to the continuing marital relationship in a healthy way.…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the relationship between marital characteristics and marital processes with marital satisfaction in a sample of 201 respondents in a study conducted by Rosen-Grandon, Myers, and Hattie (2004), it was found that 2015 gender and length of marriage contributed significantly to marital satisfaction. Conclusions drawn from the study of Ebenuwa-Okoh (2008) in Nigeria about examining the effective factors of predicting marital adjustment among married persons, showed that gender, duration of marriage, and personality types were neither correlates nor predicators of marital adjustment.…”
Section: Duration Of Marriage and Adjustmentmentioning
confidence: 99%
“…Destructive and negative communication between couples are linked to decrease in marital quality and effectiveness and to increase in divorce rates (Bradbury et al, 2000;Birditt, Brown, Orbuch and McIlvane, 2010;Stanley, Markman and Whitton, 2002) Couples are not always expected to arrive at a consensus. However, reaching a common ground and seeking ways to arrive at a consensus is necessary for a healthy relationship (Canel, 2007;Rosen-Grandon, 1998). In short, with regards to effective problem solving behaviors displaying constructive behaviors such as cooperating, making a positive communication, arguing in a calm manner and actively listening are factors that increase the effectiveness in marriages (Akçabozan and Hatipoğlu-Sümer, 2013;Birditt et al, 2010;Hacı, 2011;Özen, 2006;Tallman and Hsiao 2004).…”
Section: Introductionmentioning
confidence: 99%